A gestão do Programa Bolsa Família no município de Lavras-MG: uma análise baseada nas diretrizes nacionais e na percepção das mulheres beneficiárias do programa - Santos, Lidiane Souza (2019)
Latin American countries began adopting conditional cash transfer programs in the early twentieth century to overcome poverty, and all of them began to prioritize women as beneficiaries of the benefit. In Brazil, the Bolsa Família Program (BFP) was implemented along the same lines, where 92% of those responsible for the benefit card are women. The debate on poverty permeates the issue of gender and race, and these characteristics are considered as limiting factors for the advancement of women, both in income and in the labor market. In addition, poverty must be considered as a multidimensional phenomenon that involves not only economic but also social and political dimensions. Therefore, it is necessary to implement public policies that are intersectoral for social inclusion and effective eradication of extreme poverty. Realizing that the municipality of Lavras-MG has not seen poverty as multidimensional and invested in intersectoral policies, the aim of this study is to understand how the PBF has been managed in the municipality of Lavras-MG, based on the specifications of the Manual. BFP Management and the perception of women responsible for card ownership in relation to the opportunities to unlink the program. To understand this phenomenon, the research is a case study, qualitative, observational and descriptive approach. Its construction was supported by the triangulation of data collected from three distinct sources. The first data collection was carried out with the BFP municipal manager through a semi-structured interview, while the second data collection was conducted through conversation circles with the women responsible for card ownership at the six Centros de Referência de Assistência Social (CRAS) that existed in the municipality at the time the field research was carried out and the third data source corresponded in the production of a Field Notebook with the registration of the entire process. The technique used to perform the analysis of all these collected data was content analysis. It was observed that the management of the BFP in the municipality is deficient in several aspects, namely: control, monitoring and monitoring of beneficiary families; decentralized management; intersectoriality; use of decentralized management support systems; BFP Social Control Instance; and complementary actions. The perception of women who hold the BFP card about the municipality's performance with regard to the offer of complementary actions, corroborates the reported diagnosis, especially regarding the lack of investment in other axes such as access to services and professionalization. which causes a dependence of these families with the BFP.